THE CONTINUING EDUCATION IN THE FOREST INDUSTRY –A PREREQUISITE FOR INNOVATION (Innovation in Woodworking Industry and Engineering design, 2026)
In terms of the enhanced process of globalization and in the context of establishing a knowledge- based economy, the need for lifelong learning and continuing education is growing. Changes in management, organization of work processes, market and customer requirements, mean constant training and qualification. The Continuing education is insensibly becoming a prerequisite for the increased innovation activity of firms. In this regard, it is very important to determine the right approach for research and identifying training needs. This paper aims to provide the theoretical and practical aspects of the problem "Continuing education in Forest Industry”.